The Development of the College Students' Experience of Family Harmony Questionnaire (CSEFHQ) - Zhan, Qisheng; Wang, Qin (Frontiers in Psychology, 2021)
The experience of family harmony, as an individual's subjective evaluation of harmonious family relations, has an important influence on the development of their physical and mental health. This study aimed to develop the College Students’ Experience of Family Harmony Questionnaire (hereinafter referred to as CSEFHQ) that fitted for college students in China. On the basis of literature analysis and questionnaire survey, five pairs of opposite assessment indexes were constructed in this paper, namely Atmosphere of family (getting-along vs. conflict), Responsibility to housework (undertaking housework vs. refusing housework), Time-sharing (sharing vs. self-isolatedness), Seeking help (help-seeking vs. avoidance), Supporting family members (support-providing vs. indifference), and they are abbreviated as ARTSS. Items of this questionnaire were collected from investigation, relevant scales and discussion with experts. 562 college students were selected for the pretest and 696 for the formal test. The results showed that, except for the dimension of refusing housework which has been deleted, other dimensions remain unchanged, and the final nine dimensions accounted for 66.03% of variance variation. Furthermore, the result of confirmatory factor analysis (CFA) indicates that the model fitted well with the data in construct validity (χ2 / df = 2.71, IFI = 0.90, TLI = 0.89, CFI = 0.90, RMSEA = 0.05, SRMR = 0.05) The Cronbach's alpha (α) coefficient of this questionnaire was 0.97. The split-half reliability was 0.92 and the test-retest reliability was 0.75 for the total questionnaire. The total score of the questionnaire was significantly positively correlated with the total score of APGAR, FACESII and Index of Well-Being (r = 0.73, 0.71, 0.75, 0.51, respectively, all p < 0.01), and it had a significant negative correlation with loneliness (r = -0.56, p < 0.01). The results showed that the final structure was reasonable and reliability and validity conformed to the requirements of psychometrics. Therefore, the questionnaire developed in this study can be used as a valid instrument for assessing the experience of family harmony among college students in China.